2020
DOI: 10.1111/brv.12653
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking body sizes in response to warming: explanations for the temperature–size rule with special emphasis on the role of oxygen

Abstract: Body size is central to ecology at levels ranging from organismal fecundity to the functioning of communities and ecosystems. Understanding temperature‐induced variations in body size is therefore of fundamental and applied interest, yet thermal responses of body size remain poorly understood. Temperature–size (T–S) responses tend to be negative (e.g. smaller body size at maturity when reared under warmer conditions), which has been termed the temperature–size rule (TSR). Explanations emphasize either physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
234
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(250 citation statements)
references
References 216 publications
13
234
3
Order By: Relevance
“…Second, large individuals are likely more susceptible to oxygen limitation and therefore they could experience a greater reduction in aerobic scope with warming. This prediction supports the idea that oxygen limitation is at least partly responsible for driving the reduction of body size in response to global warming ( 32 , 45 , 49 ). Finally, risks of oxygen limitation will be greater in aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, large individuals are likely more susceptible to oxygen limitation and therefore they could experience a greater reduction in aerobic scope with warming. This prediction supports the idea that oxygen limitation is at least partly responsible for driving the reduction of body size in response to global warming ( 32 , 45 , 49 ). Finally, risks of oxygen limitation will be greater in aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 87%
“…A secondorder extrapolation of our model is that, in aquatic ectotherms, larger individuals likely experience greater oxygen limitation whenever temperatures are warmer, or activity levels are higher. Therefore, large animals may have some aerobic scope left to fuel activity, growth, and reproduction in cold waters but not in warmer waters--a prediction that is consistent with the temperature-size rule, i.e., the tendency of many ectotherms to grow to smaller final sizes when reared in warmer temperatures (45). Thus, Forster et al (46) found that the temperature-size rule is more pronounced in aquatic than terrestrial species.…”
Section: Discussionmentioning
confidence: 92%
“…Because we control for spatial autocorrelation in the data, we can tentatively conclude that these associations do not simply reflect other ecological responses to elevated temperatures with consequences for lateral plate number that also correlate with body size, such as predation. However, we believe the most parsimonious interpretation of the results are that (a) A decline in body size is associated with elevated average temperatures, which shows a temporal association (this study) and a spatial association (Smith et al, 2020b), and reflects a well-established ecological relationship between body size and temperature (Verberk et al, 2021). (b) Lateral plate number is strongly associated with body size in sticklebacks, which is associated with swimming efficiency (Bergstrom, 2002;Smith et al, 2020b).…”
Section: Deviance Information Criterionmentioning
confidence: 64%
“…Conversely, a switch from 91% dominance by lowplated sticklebacks to dominance by completely plated fish in Lake Washington was associated with a 30% increase in mean fish length (Kitano et al, 2008). (Verberk et al, 2021). The causal explanation for this relationship is unclear, but applies across a range of endotherms and ectotherms, including fishes (Morris et al, 2017;Verberk et al, 2021).…”
Section: Deviance Information Criterionmentioning
confidence: 99%
“…Annual mean temperature can also affect reproductive output, for instance mild winter conditions can induce an increase in body condition, and consequently higher reproduction rates (Brischoux et al, 2016). These temperature effects on ectotherms also lead to the expectation that individual reproduction probabilities change over latitudinal or altitudinal gradients due to changes in temperature throughout the reproductive season: when summer seasons become shorter (e.g., pole-wards or at higher altitudes), reproduction could be expected to become less frequent, while energy maybe spent more on an increase of body mass (Buckley et al, 2012;Rutschmann et al, 2020;Verberk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%